Inovasi Media Pembelajaran 3D melalui Experiential Learning: Sebuah Strategi untuk Meningkatkan Motivasi dan Berpikir Kritis Siswa dalam Pembelajaran Sains - Fannya Nadim Rooshadiya; Arif Widiyatmoko; Ellianawati (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to investigate the effectiveness of 3D media based on experiential learning in enhancing students’ learning motivation and critical thinking skills on the topic of the human respiratory system. The media was developed using the ADDIE model and tested through a quasi-experimental design involving eighth-grade students divided into control and experimental groups. Data were collected through pretest, posttest, questionnaires, observation, and interviews. The experimental group used 3D web-based media, while the control group received conventional instruction. Results showed a significant increase in the experimental group’s motivation, especially in interest, effort, persistence, and self-confidence. Critical thinking also improved, particularly in argumentation and implementation. Welch’s t-test showed a significance value of 0.000, and n-gain analysis revealed higher effectiveness in the experimental group, with learning motivation categorized as high (n-gain = 0.7) and critical thinking as moderate (n-gain = 0.5), compared to low in the control group (n-gain = 0.3). The integration of interactive 3D visualization with experiential learning allowed students to better connect theoretical concepts to real-life applications. These findings suggest that experiential learning-based 3D media is a powerful tool to improve motivation and critical thinking in science education.